Exploring Intention In Using Quick Response Code Indonesian Standard: Technology Acceptance Model Approach - Hartutik; Dwi Nita Aryani; R. Melda Maesarach; Rosnia Masruki; Ahmad Fauzan (LPPM Universitas Terbuka, 2024)
Non-Indexed Publication